Confessions of a murder suspect - Patterson, James, 1947- (Little, Brown, 2012)
Tandy Angel is, along with her brothers, a suspect in their parents' murder but having grown up under Malcolm and Maud Angel's perfectionist demands, Tandy decides she must clear the family name no matter what.